THE POTENTIAL OF Azadirachta indica (NEEM TREE) LEAVES FOR BIOETHANOL PRODUCTION USING Zymomanas mobilis AS FERMENTING ORGANISMS - Grace, Atinuke Felix; Ruwa, Abdulhamid Musa Ruwa; Hafsah, M. A.; Kaltum, U. M.; Ali, A. A.; Adeboye, M. M.; Musa, I.; Falmata, B. M. D.; Usman, A. B.; Hauwa, M. A.; Hosea, S. H.; Aisha, L. K. (FUDMA JOURNAL OF SCIENCES, 2022)
Bioethanol is a renewable energy produced from lignocellulosic biomass mainly by the fermentation process. It is used as an alternative to fossil fuel which doesn’t contribute to global warming. This research work was carried out to determining the potential of Neem tree leaves for bioethanol production. The process used in this study include pretreatment, hydrolysis fermentation and distillation. Hot water and Acid methods were used for the pretreatment. The hydrolysis of the substrate was carried out using Aspergillus niger for five days. Benedict test method was used to determine the reducing sugar concentration of the hydrolysate. The highest yield of 1500-2000 (mg/dl) was obtained equally for both the pre-treatment method. After hydrolysis, fermentation process was carried out for seven days using Zymomonas mobilis to ferment the hydrolysate. The fermented broth was separate using fractional distillation. Acid potassium dichromate was used to determine the concentration of the bioethanol produced. The results obtained shows that liquid hot water pretreatment produced the highest yield of 0.294±0.882 (mg/L) whereas alkaline method produced 0.282±.882 (mg/L) yield. Gas chromatography and mass spectroscopy analysis was also carried out to determine the presence of volatile compounds in the bioethanol produced. The highest volatile compound was Ethanol with 33.12% where Butyl Glycol was found to be least volatile compound with 6.22%. This result shows that Neem tree leaves is a good biomass for bioethanol production and pretreatment using Hot water method produced more bioethanol than Alkaline method of pretreatment.